Business enterprise architecture in fitness center using the open group architecture framework - Jonathan, Eric; Andry, Johanes Fernandes (Institute of Advanced Engineering and Science, 2024)
Sports currently have an impact on human life, especially in the health sector. One way of exercising that is popular with many people today is by exercising at the fitness center. One of them is a fitness center located in Bandung. This research aims to obtain design results that can adapt business processes in fitness centers and can help the company's performance so that its vision and mission are achieved. The current business process is still experiencing problems because business has not yet been integrated with information technology (IT), so a business process proposal was made using the business architecture method. By conducting interviews and observations, data can be collected. From this data, it can be seen that business implementation in fitness centers is not yet optimal, so it is necessary to develop information system technology that is in line with the company's business. This technology development is based on business architecture which produces a company blueprint and is assisted by the open group architecture framework (TOGAF) which can help analyze company needs. The results of this research are in the form of recommendations which will later be proposed so that benefits for the company can be achieved more quickly.